MENGINTEGRASIKAN EKONOMI HIJAU DAN KEBERLANJUTAN: KAJIAN LITERATUR ATAS PRAKTIK TERBAIK DI BERBAGAI NEGARA - Fittry Megasari Sijabat (Prosiding Seminar Nasional Indonesia, 2025)
This literature study aims to explore and summarize the best practices that have been adopted by various countries in integrating the green economy with the concept of sustainability. This research uses the literature method. The results recommend increased international cooperation and knowledge sharing to accelerate the transition to a sustainable green economy, ensure inclusive economic growth, and maintain environmental integrity for current and future generations.